Implikasi Reposisi Manajerial BUMN Terhadap Pertanggungjawaban Tindak Pidana Korupsi - Jakobus Anakletus Rahajaan; Sarifa Niapele (Journal of Business Application, 2025)
This study analyzes the repositioning of State-Owned Enterprise (SOE) management following the enactment of Law No. 1 of 2025 on SOEs, and its implications for criminal liability in corruption cases. Employing a normative juridical method with statutory and conceptual approaches, this research offers a prescriptive perspective in response to public concerns regarding the exclusion of SOE executives from the category of state administrators. The findings reveal that such concerns are unfounded, as the new provisions in fact strengthen the immunity of SOE management from political interference by state officials, which is often a source of corruption. Although Law No. 1 of 2025 does not explicitly regulate the nexus between the management of state-derived finances and criminal liability for corruption, SOEs as legal entities (rechtpersoon) remain subject to criminal prosecution when implicated in acts of corruption. Corporate criminal liability in corruption has been clearly stipulated in existing anti-corruption legislation. This study contributes new insights to the discourse on SOE governance law, demonstrating that the new regulation serves not as a weakening, but rather as a reinforcement of accountability and the independence of SOE management.